2018
DOI: 10.1016/j.biopha.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecules derived from tRNA and snoRNA: Entering the degradome pool

Abstract: Molecules built of RNA have been the subjects of numerous studies, which have made known new functions and structures that these molecules can create. In recent years, thanks to next-generation sequencing, it is possible to observe very small RNAs and the number of newly discovered RNA molecules is rapidly increasing. Among other small oligonucleotides, structures derived from tRNA and snoRNA molecules have been observed, and these molecules were determined to not be precursors of known RNA molecules. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Recent genomic studies using parallel high throughput technologies like Next-generation sequencing (NGS) and microarrays have revealed that the molecular heterogeneity of CLL is further complicated by alterations in gene expression patterns and epigenetic regulatory events; and abundance of long noncoding RNAs (lncRNA) and small noncoding RNAs (sncRNAs) such as microRNAs (miRs), tRNA, piRNA, snoRNA, etc 4,5 . A plethora of studies on transcriptional profiling of miRs have identified a variety of differentially expressed miRs (DEMs) in CLL [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent genomic studies using parallel high throughput technologies like Next-generation sequencing (NGS) and microarrays have revealed that the molecular heterogeneity of CLL is further complicated by alterations in gene expression patterns and epigenetic regulatory events; and abundance of long noncoding RNAs (lncRNA) and small noncoding RNAs (sncRNAs) such as microRNAs (miRs), tRNA, piRNA, snoRNA, etc 4,5 . A plethora of studies on transcriptional profiling of miRs have identified a variety of differentially expressed miRs (DEMs) in CLL [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Some snoRNAs were differentially expressed between the various immunized groups (Table S5). Despite the variety in chicken breeds and differences in maintenance conditions, some of these differences may be caused by the recognition of snoRNA derivatives by the Transcript Clusters optimized to detect snoRNA molecules [37,38]. Moreover, Transcript Clusters optimized for detection of certain mRNA can detect also regulatory RNA made from pseudogenes [39].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been shown that snoRNAs can be a target of RNase P in some species during snoRNA maturation (Coughlin et al, 2008;Marvin et al, 2011). We know now that snoRNAs molecules can be cleaved into snoRNA fragments (snoRFs) but the enzyme(s) responsible for their cleavage remains poorly studied (Światowy and Jagodzińśki, 2018). snoRFs are aberrantly present in several pathologies such as cancer and neurodegeneration diseases (Falaleeva and Stamm, 2013;Patterson et al, 2017;Romano et al, 2017;Światowy and Jagodzińśki, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We know now that snoRNAs molecules can be cleaved into snoRNA fragments (snoRFs) but the enzyme(s) responsible for their cleavage remains poorly studied (Światowy and Jagodzińśki, 2018). snoRFs are aberrantly present in several pathologies such as cancer and neurodegeneration diseases (Falaleeva and Stamm, 2013;Patterson et al, 2017;Romano et al, 2017;Światowy and Jagodzińśki, 2018). Thus, RNase P could somehow participate in limiting snoRNA fragmentation to preserve homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation